Immune and Clinical Features of CD96 Expression in Glioma by in silico Analysis - Zhang, Qiang; Zhong, Hua; Fan, Yinchun; Liu, Qian; Song, Jiancheng; Yao, Shengtao; Cao, Fang (Frontiers in Bioengineering and Biotechnology, 2020)
CD96 is a novel immune checkpoint and an attractive key target for cancer immunotherapy. To take an integrative investigation of CD96 in glioma, a total of 1024 RNA and clinical data were enrolled in this study, including 325 samples from the Chinese Glioma Genome Atlas (CGGA) database and 699 samples from The Cancer Genome Atlas (TCGA) dataset. We found that CD96 had a consistently positive relationship with glioblastoma (WHO IV grade) and highly enriched in IDH-wildtype and mesenchymal subtype glioma. GO enrichment and GSVA analyses suggested that CD96 was more involved in immune functions, especially related to T cell-mediated immune response in glioma. Subsequent immune infiltration analysis manifested that CD96 expression was positively correlated with infiltrating levels of CD4+ T and CD8+ T cells, macrophages, neutrophils, and dendritic cells (DCs) in glioblastoma multiforme (GBM) and lower-grade glioma (LGG). Additionally, CD96 was tightly associated with other immune checkpoints including PD-1, CTLA-4, TIGIT, and TIM-3. Univariate and multivariate Cox analysis demonstrated that CD96 acts as an independent indicator of poor prognosis in glioma. These results present favorable application prospects for further immunotherapeutic in glioma patients.